Use of Real-Time PCR To Process the First Galactomannan-Positive Serum Sample in Diagnosing Invasive Aspergillosis - Millon, Laurence (American Society for Microbiology, 2005)
Positive galactomannan (GM) antigenemias are included as a microbiological item in the diagnosis of probable or possible invasive aspergillosis (IA). Because false-positive GM results frequently occur, at least two positive results on two different samples are required. Waiting for clinical specimens can delay the initiation of treatment. As an alternative, we wondered whether detection of circulating Aspergillus DNA on the first positive GM serum sample could aid in diagnosing IA. Therefore, we retrospectively screened the first GM-positive serum samples from 29 patients from our hematology unit for Aspergillus DNA using real-time PCR. We compared the real-time PCR results with the final classification of proven, probable, and possible IA according to consensual criteria. No clear correlation between PCR results and the classification with the medical files could be shown. However, a positive PCR result was associated with a poor prognosis (Fisher's test; P = 0.01). Our preliminary data suggest that a positive PCR result could indicate a more advanced stage of the disease. Therefore, concomitant positive PCR and GM results may justify the initiation of antifungal therapy in neutropenic patients. In contrast, a negative PCR on the first positive GM sample may argue for postponing costly antifungal administration until additional arguments for the diagnosis of IA are presented.